2014
DOI: 10.1016/j.bbadis.2014.09.016
|View full text |Cite
|
Sign up to set email alerts
|

H63D HFE genotype accelerates disease progression in animal models of amyotrophic lateral sclerosis

Abstract: Keywords:H63D HFE SOD1(G93A) ALS Iron Oxidative stress Gliosis H63D HFE is associated with iron dyshomeostasis and oxidative stress; each of which plays an important role in amyotrophic lateral sclerosis (ALS) pathogenesis. To examine the role of H63D HFE in ALS, we generated a double transgenic mouse line (SOD1/H67D) carrying the H67D HFE (homologue of human H63D) and SOD1(G93A) mutations. We found double transgenic mice have shorter survival and accelerated disease progression. We examined parameters in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 74 publications
(120 reference statements)
1
23
1
Order By: Relevance
“…Conversely, in patients with SOD1 mutations the presence of a G allele was found to be significantly associated with a longer survival. This finding is in contrast with the reported shorter survival in the double transgenic mouse line (SOD1/H67D) (Nandar et al, 2014), highlighting the possibility that genetic interactions in mice compared with humans are biologically different. However, because of the small number of patients carrying a SOD1 mutation in this series, our finding should be considered with caution, because of the possibility of a type 1 error.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Conversely, in patients with SOD1 mutations the presence of a G allele was found to be significantly associated with a longer survival. This finding is in contrast with the reported shorter survival in the double transgenic mouse line (SOD1/H67D) (Nandar et al, 2014), highlighting the possibility that genetic interactions in mice compared with humans are biologically different. However, because of the small number of patients carrying a SOD1 mutation in this series, our finding should be considered with caution, because of the possibility of a type 1 error.…”
Section: Discussioncontrasting
confidence: 90%
“…The authors also found that the presence of the G allele was associated with a reduction of SOD1 activity in the muscle and that SOD1 protein expression was negatively associated with total disease duration in ALS patients. In a subsequent article, the same group reported that a double transgenic mouse line (SOD1/H67D) carrying the H67D HFE (homolog of human H63D) and SOD1 (G93A) mutations have a shorter survival and an accelerated disease progression (Nandar et al, 2014); they therefore concluded that when HFE is combined with a mutation in an ALS gene the disease duration could be negatively impacted. The authors suggested that H63D HFE polymorphism can modify ALS pathophysiology via pathways involving oxidative stress, gliosis, and disruption of cellular functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human brain tissue (IRB# 40726) was obtained and sectioned in 5‐micron slices. Immunohistochemistry and immunofluorescence was performed as previously described (Connor et al, ; Nandar et al, ). Briefly, slides were deparaffinized and hydrated, performing antigen retrieval with 10mM citrate buffer, pH 6.0.…”
Section: Methodsmentioning
confidence: 99%
“…The H63D mutation and its interaction with other HFE mutations and neurodegenerative disorders remain under investigation (Nandar et al 2014; Ali-Rahmani et al 2014b; Xia et al 2015; Mariani et al 2013; Pulliam et al 2003; Gazzina et al 2015). The MRI data presented here demonstrate that there is an HFE genome related reduction in transverse R 2 in H63D human and H67D mouse carriers compared to WT-HFE controls.…”
Section: Discussionmentioning
confidence: 99%